Gender differences on lower limb coordination during eliteplayers jump - Castro, M. A.; Janeira, M. A.; Mendes, R.; Fernandes O.; Ferreira, N. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
The results from an experimental analysis of the jump in basketball female and male players are presented. Coordination of seventeen lower limb is analyzed in a high risk movement frequently performed by athletes during jump It is showed that on the sample studied several differences on relative phase are found entailing particularly transverse movement plane of knee. These results show that during some core moments of the jump, gender can influence the lower limb joint coordination. The comparison of relative phase shows a female propensity for moving in less synergy on jump reception. Such findings highlight the need for including on preparation program of athletes a prevention plan that is not necessarily identical on both genders.